2006
DOI: 10.4049/jimmunol.177.11.7656
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Th2 Cell Development by Polycomb Group Gene bmi-1 through the Stabilization of GATA3

Abstract: The Polycomb group (PcG) gene products regulate the maintenance of the homeobox gene expression in Drosophila and vertebrates and also the cell cycle progression in thymocytes and Th2 cell differentiation in mature T cells. We herein studied the role of PcG gene bmi-1 product in Th1/Th2 cell differentiation and found that Bmi-1 facilitates Th2 cell differentiation in a Ring finger-dependent manner. Biochemical studies indicate that Bmi-1 interacts with GATA3 in T cells, which is dependent on the Ring finger of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 57 publications
2
52
0
Order By: Relevance
“…2D, 2E). This result is similar to that of Bmi-1-deficient Th2 cells (44). Therefore, Ring1B may cooperate with Bmi-1 to control the stability of GATA3 protein and facilitate Th2 cell differentiation.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…2D, 2E). This result is similar to that of Bmi-1-deficient Th2 cells (44). Therefore, Ring1B may cooperate with Bmi-1 to control the stability of GATA3 protein and facilitate Th2 cell differentiation.…”
Section: Discussionsupporting
confidence: 73%
“…We previously reported that Mel-18 and Bmi-1 controls Th2 cell differentiation through distinct mechanisms; namely, Mel-18 regulates GATA3 transcription, and Bmi-1 regulates the stability of GATA3 protein (43,44). In this paper, we show that another PcG molecule, Ring1B, plays a role in Th2 cell differentiation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In peripheral CD4 T cells, the activation of STAT6 induces highlevel GATA3 mRNA expression (12), and we and others have recently reported that STAT6 binds to specific regions of the GATA3 gene to regulate its transcription (13,14). In addition, the protein expression of GATA3 in Th2 cells is regulated by various posttranscriptional mechanisms (15)(16)(17). Changes in histone modifications, such as H3-K9/14 acetylation and H3-K4 methylation at the Th2 cytokine gene loci, occur during Th2 cell differentiation (18)(19)(20), and this is induced primarily by GATA3 in both CD4 and CD8 T cells (21).…”
mentioning
confidence: 99%
“…Enforced expression of GATA3 has also been reported to endogenously upregulate GATA3 expression [36]. In addition, the amount of GATA3 protein in Th2 cells is regulated by various postranscriptional mechanisms [37][38][39]. Furthermore, high-level expression of GATA3 is essential for the production of large amounts of Th2 cytokines in established Th2 cells [11,[40][41][42].…”
Section: Gata3 Plays Roles In Various Tissues As Well As the Immune Smentioning
confidence: 99%